University students' belief in "rape myths": a cross-cultural study - Diedericks, Juane (University of the Free State, 2003)
The increasing prevalence of rape in South Africa is a disconcerting phenomenon. Various theories on the causative factors of rape are discussed in the light of the relevant literature. It becomes evident from the existing literature that one’s attitudes regarding rape, the rapist and the rape victim are decisive factors in determining one’s propensity to engage in sexual aggression. The construct attitude as well as theories concerning attitude development and change are also explored in the literature review. Rape-tolerant beliefs and negative attitudes towards the rape victim are important cognitive factors to take into account when examining rape. These permissive attitudes towards sexual aggression are collectively termed rape myths. Rape myths play a significant role in the recovery process of the rape victim, the probability of convicting the rapist and determining which incidences of sexual aggression will be defined as rape. Relatively few studies on rape myths have been performed in South Africa and there is a substantial lack of cross-cultural studies in this regard. The main objective of this study is to determine the extent to which students at the University of the Free State adhere to rape myths. The influence of gender and race in determining rape myth acceptance was examined. A non-experimental research design was employed, with gender and race as the independent variables and rape myths as the dependent variable. The research participants consisted of 486 students from the University of the Free State. The participants were obtained by randomly selecting three faculties, from which several classes were identified to take part in the study. There were 166 male and 320 female participants, of which 250 are white and 236 are black. A biographical questionnaire was constructed to determine the demographic variables of gender, race, language and age. The Illinois Rape Myth Acceptance Scale (IRMA) was employed to assess rape myth acceptance. As the IRMA was constructed in English, it was translated into Afrikaans by means of back-translation. The respondents could participate freely in the study and could complete the questionnaires in their language of choice. As the nature of the topic is sensitive, the respondents remained anonymous. The reliability of the IRMA was calculated by means of Cronbach alpha coefficients and satisfactory reliabilities were obtained. A multivariate analysis of variance was performed to determine the extent to which the independent variables (gender, race) influence the dependent variable (rape myth acceptance). One-way analyses of variance were conducted for each of the four combinations of the independent variables to determine their combined effect on rape myth acceptance. The most important research findings are the following: • Males exhibited consistently greater acceptance of rape myths than females. • The variable of race did not account for consistent differences in rape myth acceptance. • The simultaneous effect of gender and race on rape myth acceptance exhibited that black male respondents accepted the most rape myths and black female respondents accepted the least rape myths. One of the limitations to this study is the limited generalisability of the findings as all the participants are university students. Similar studies, with respondents from various sectors of the general public may expand the generalisability of the research findings. Future studies could also explore the influence of age, occupation or contact with sexual aggression on rape myth acceptance.

Die hoë voorkoms van verkragting is ‘n kommerwekkende verskynsel in Suid-Afrika. Verskeie teorieë wat die oorsaaklike faktore van verkragting uitlig, word aan die hand van toepaslike literatuur bespreek. Hieruit blyk dit dat 'n persoon se houdings en oortuigings oor verkragting en die verkragtingslagoffer ‘n groot bydraende rol speel in die pleging van dié misdaad. Die konsep houdings, asook die ontwikkeling en verandering van houdings word breedvoerig volgens die literatuur bespreek. Persone met permissiewe houdings teenoor seksuele geweld blyk meer geneig te wees tot seksueel aggressiewe gedrag. Hierdie oortuigings en houdings oor verkragting word kollektief verkragtingsmites genoem en dit speel ‘n groot rol in die herstelproses van die slagoffer, die waarskynlikheid dat die verkragter skuldig bevind sal word en bepaal tot ‘n groot mate watter insidente van seksuele aggressie as verkragting geïdentifiseer sal word. Daar is betreklik min studies reeds in Suid-Afrika gedoen oor verkragtingsmites en daar is veral ‘n gebrek aan kruis-kulturele studies in hierdie verband. Die hoofdoelwit van hierdie studie is om te bepaal tot watter mate studente aan die Universiteit van die Vrystaat verkragtingsmites ondersteun. Daar is ook ondersoek of daar beduidende verskille ten opsigte van geslag en ras bestaan met betrekking tot die ondersteuning van verkragtingsmites. Daar is van nie-eksperimentele navorsing gebruik gemaak, met geslag en ras as die onafhanklike veranderlikes teenoor verkragtingsmites as die afhanklike veranderlike. Die ondersoekgroep van hierdie studie het bestaan uit 486 studente aan die Universteit van die Vrystaat. Hierdie studente is verkry deur drie fakulteite ewekansig te trek en groepe te selekteer om aan die studie deel te neem. Daar was 166 manlike en 320 vroulike respondente, van wie 250 blank is en 236 swart is. ‘n Biografiese vraelys is opgestel om die demografiese veranderlikes van geslag, ras, taal en ouderdom te bepaal. Die Illinois Rape Myth Acceptance (IRMA) vraelys is geïmplementeer vir die meting van verkragtingsmites. Aangesien laasgenoemde vraelys oorspronklik in Engels opgestel is, is dit vanuit Engels na Afrikaans vertaal deur middel van die terugvertalingsmetode. Die respondente kon die vraelys vrywillig voltooi in die taal van hul keuse. Aangesien die onderwerp van die vraelys sensitief van aard is, is hulle anonimiteit verseker. Die betroubaarheid van die IRMA is vir die Afrikaanse en die Engelse vertaling met behulp van Cronbach se alfa-koëffisiënt bereken en bevredigende toetsbetroubaarhede is verkry. ’n Meervoudige variansie-analise is uitgevoer om te bepaal of die onafhanklike veranderlikes (geslag, ras) ’n beduidende invloed uitoefen op die afhanklike veranderlike (verkragtingsmites). Eenrigting variansie-analises is uitgevoer vir elk van die vier kombinasies van geslag en ras om hul gekombineerde effek op verkragtingsmites te bepaal. Die belangrikste navorsingsbevindinge is die volgende: • Mans het deurgaans beduidend hoër aanvaarding van verkragtingsmites as vrouens getoon. • Ras het nie ’n konsekwente invloed op die aanvaarding van verkragtingsmites uitgeoefen nie. • Die gesamentlike effek van geslag en ras op verkragtingsmites het getoon dat swart mans die meeste, en swart vrouens die minste mites aanvaar. Een van die studie se tekortkominge is die beperkte veralgemeenbaarheid van hierdie resultate na die algemene bevolking, omdat al die deelnemers aan die studie studente is. ‘n Soortgelyke studie met respondente uit verskillende sektore van die algemene publiek kan tot ‘n groter veralgemeenbaarheid van resultate lei. Toekomstige studies kan die invloed van veranderlikes soos ouderdom, beroep of kontak met ’n slagoffer van verkragting op verkragtingsmites ondersoek.
Dissertation (M.Sc. (Clinical Psychology))--University of the Free State, 2003
Keywords: Rape; Rape myth; Rape myth acceptance; Cross-cultural study; Gender; Race; University students; Attitudes; Analysis of variance; Attitude (Psychology); Rape -- Psychological aspects; Rape -- Mythology; College students -- South Africa -- Bloemfontein -- Attitudes